1995
DOI: 10.1016/0014-5793(95)00079-o
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the DNA binding domain of a nucleoid‐associated protein, H‐NS, from Escherichia coli

Abstract: The three-dimensional structure of the C-terminal domain (47 residues) obtained from the hydrolysis of H-NS protein with bovine trypsin was determined by NMR measurements and distance geometry calculations. It is composed of an antiparallel B-sheet, an a-helix and a 31o-helix which form a hydrophobic core, stabilizing the whole structure. This domain has been found to bind to DNA. Possible DNA binding sites are discussed on the basis of the solution structure of the C-terminal domain of H-NS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 27 publications
8
129
0
Order By: Relevance
“…The two helices are perpendicular to and packed against each other through hydrophobic interactions among residues Ile83, Arg84, Ala87, Val94, Ile100, and Val104 and aromatic stacking between Trp86 and Tyr108. The structure of Lsr2C is unique and distinct from that of H-NS, which consists of two short β-strands and an α-helix linked by a loop (40,41). A protein structure database search using DALI did not identify any structure with a z-score over 3.0.…”
Section: Lsr2mentioning
confidence: 95%
“…The two helices are perpendicular to and packed against each other through hydrophobic interactions among residues Ile83, Arg84, Ala87, Val94, Ile100, and Val104 and aromatic stacking between Trp86 and Tyr108. The structure of Lsr2C is unique and distinct from that of H-NS, which consists of two short β-strands and an α-helix linked by a loop (40,41). A protein structure database search using DALI did not identify any structure with a z-score over 3.0.…”
Section: Lsr2mentioning
confidence: 95%
“…2). The DNA-binding region was identified by showing that a C-terminal 47-amino-acid fragment of proteolytically digested H-NS protein binds to curved DNA, although with much lower affinity than intact H-NS (Shindo et al, 1995). This DNA-binding domain appears to be unique as its three-dimensional structure does not show any similarity to other DNA-binding proteins (Fig.…”
Section: Structure and Isoforms Of H-nsmentioning
confidence: 99%
“…eco: E. coli; shi: Shigella flexneri; sty : Salmonella typhimurium; sma: Serratia marcescens; pvu : Proteus vulgaris; hin: Haemophilus influenzae; Asterisks indicate identical amino acids in all sequences, and full points indicate conserved amino acids. The E. coli H-NS dimerization domain (Williams et al, 1996) and the DNA-binding domain and its secondary structure (Shindo et al, 1995) are indicated above the sequence. Jagged lines, ␤1 and ␤2 indicate ␤-sheets; solid lines indicate L1, L2 and L3; loops indicate ␣-helix.…”
Section: Figmentioning
confidence: 99%
“…Moreover, using FROST, a fold-recognition method (http://www-mig. jouy.inra.fr), this domain was predicted to share the same three-dimensional structure as the E. coli H-NS C-domain resolved previously by NMR (Shindo et al, 1995). Finally, the expression of the strain Y1000 protein structural gene in an E. coli mutant fully reversed additional hns-related phenotypes, for example, the loss of motility on semi-solid medium and the ability to use b-glucoside as a sole carbon source, as observed previously with other H-NS-like proteins (Goyard & Bertin, 1997;Bertin et al, 1999Bertin et al, , 2001Tendeng et al, 2000).…”
mentioning
confidence: 96%